Cobalt‐Catalyzed Reductive Cross‐Coupling Between Styryl and Benzyl Halides. Issue 2 (2nd December 2016) - Cai, Yingxiao; Benischke, Andreas D.; Knochel, Paul; Gosmini, Corinne
Abstract: A simple and efficient protocol for the direct reductive cross‐coupling between alkenyl and benzyl halides using a Co/Mn system has been developed. This reaction proceeds smoothly in the presence of [CoBr2 (PPh3 )2 ] as the catalyst, with NaI as an additive in acetonitrile with a broad scope of functionalized alkenyl and benzyl halides. Different functional groups are tolerated on both coupling partners, thus, significantly extending the general scope of transition‐metal‐catalyzed benzylation of alkenyl halides. Moderate to excellent yields were also obtained. From a mechanistic point of view, a radical chain mechanism was proposed. This reaction is stereospecific and some studies suggest the retention of the double‐bond configuration. Abstract : Crossing benzyl and styryl : An efficient Co‐catalyzed reductive cross‐coupling of benzyl chlorides with alkenyl bromides has been achieved. The complete retention of the double‐bond configuration was observed and moderate to excellent yields were obtained in mild conditions.